pengaruh infrastruktur energi terhadap pertumbuhan ekonomi di kabupaten/kota provinsi riau - martina lucas (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2022)
Energy infrastructure is an engineering and construction activity for the management of natural resources used in industrial processes and for power generation. This study was conducted to examine the effect of energy infrastructure on economic growth. Energy infrastructure is measured by the electrification ratio (X1) which is the dependent variable. This study also uses control variables, namely road infrastructure (X2) and water infrastructure (X3). The type of research used is descriptive research. The data that is processed is the data of PLN electricity, non PLN electricity and households. While the published data is data from the Central Statistics Agency in the form of data on road infrastructure and clean water infrastructure for 2016-2020. The analysis technique used is panel data regression analysis. The results showed that partially significant variables affecting economic growth were the electrification ratio (X1) and water infrastructure (X2) variables. While the road variable (X3) partially has no significant effect on economic growth in Riau Province. Furthermore, the variables of electrification ratio (X1), road infrastructure (X2), and clean water infrastructure (X3) together (simultaneously) have an influence on economic growth in Riau Province. The contribution of each independent variable is 99.6% and the remaining 0.4% is explained by other variables not discussed in this study. While the road variable (X3) partially has no significant effect on economic growth in Riau Province. Furthermore, the variables of electrification ratio (X1), road infrastructure (X2), and clean water infrastructure (X3) together (simultaneously) have an influence on economic growth in Riau Province. The contribution of each independent variable is 99.6% and the remaining 0.4% is explained by other variables not discussed in this study. While the road variable (X3) partially has no significant effect on economic growth in Riau Province. Furthermore, the variables of electrification ratio (X1), road infrastructure (X2), and clean water infrastructure (X3) together (simultaneously) have an influence on economic growth in Riau Province. The contribution of each independent variable is 99.6% and the remaining 0.4% is explained by other variables not discussed in this study.